THE POLITICS OF APPOINTING POLITICAL AND CARREER DIPLOMATS’ IN NIGERIA: Understanding the Nexus - MAHDI ABUBAKAR ABBA (International Studies Journal)
Diplomatic appointment in Nigeria is an elite phenomenon and shrouded with many secrecies. The process of selection and confirmation of ambassadors for onward posting to their receiving states is a complex process. Though, there are literature on diplomacy and international relations with respect to foreign policy, but there are limited literature on the selection and confirmation process of ambassadors’ in Nigeria. This paper examines the complex process of ambassadorial appointments and their role in promoting national interest of their respective states in foreign land. The paper also examines the relationship that exist between the two categories of ambassadors and the rights and privileges they enjoyed while discharging their duties in foreign land. The author used content analysis and interview of some professional experts in the field of law making and international relations. The findings of the paper shows that diplomatic appointment in Nigeria is complex. Both political and career ambassadors are deployed by the federal government of Nigeria through the ministry of foreign affairs in foreign land for representation and promotion of national interest. Diplomatic appointment in Nigeria is exclusively preserved for the President. However, it requires legislative (Senate) confirmation and security clearance. The paper recommends that the Nigerian government need to review the application of federal character principle and quota system in the appointment of ambassadors.